SAT0688 Joint involvement in patients with knee and hip oa scheduled for surgery: multi-joint oa, the rule not the exception?. (15th June 2017) - Badley, EM; Yip, C; Power, JD; Gandhi, R; Mahomed, N; Davey, JR; Syed, K; Rampersaud, YR; Veillette, C; Perruccio, AV
Abstract : Background: Multijoint involvement in osteoarthritis (OA) has long been documented clinically and in the literature. Even so, the vast majority of OA research has focused on OA in individual joints, particularly the knees, hips or hands. In many "joint-specific" studies, the presence of multijoint symptoms are either ignored or peripherally considered in descriptive and analytical work. The implicit assumption is often that OA is OA, irrespective of whether a single joint or several joints are involved. Objectives: To document the occurrence of multijoint symptoms in a clinical sample of individuals with knee and hip OA scheduled for orthopaedic surgery. To examine the joint sites involved and investigate whether the extent of joint involvement is related to demographic and health characteristics. Methods: Patients scheduled for total knee or hip replacement for end-stage OA were consecutively recruited from an academic hospital in Toronto, Canada. A health questionnaire completed prior to surgery captured demographic characteristics (age, sex), symptomatic joints other than the surgical joint (right and left shoulders, elbows, wrists, hands, hips, knees, feet, ankle, neck and back), body mass index (BMI), comorbidities (hypertension, depression, diabetes, migraine headaches, cancer, respiratory disease, heart disease, stomach/bowel disease, stroke) and WOMAC hip- and knee-specific pain and function. Results: Study questionnaires were completed by 366 hip and 407 knee patients. The mean age of the sample was 65 years (SD=9.2; range 38–89 years), 57% were female. The most frequently reported symptomatic joints among knee patients were the contralateral knee (53.2%), one or both hands (32.1%), and the upper-, mid- or lower-back (31.0%), and among hip patients were one or both knees (49.4%), the back (36.6%), and the contralateral hip (21.3%). The overall mean number of symptomatic joints other than the surgical joint was 3.0 (SD=3.2; range 0–17). Only 19.0% reported the surgical joint as the only symptomatic joint; 23.0% reported 5 or more additional symptomatic joints. Mean hip/knee-specific pain and function scores were significantly worse with increasing symptomatic joint count (p<0.01). Additional symptomatic joints were significantly more frequent in women than men; mean count 3.6 vs. 2.3 (p<0.01). No significant difference in mean joint count (p=0.64) was observed by age. Similarly, no difference was found by BMI (i.e. overweight/obese vs. normal); p=0.24 for mean count. However, the number of co-occurring conditions increased with increasing joint count: 27.2% reported 2+ co-occurring conditions among those with 1–4 symptomatic joints, and 42.8% among those with 5+ symptomatic joints (p<0.01). Conclusions: In this clinical OA sample, the "average" patient reported multiple symptomatic joints. Increasing age was not associated with increasing frequency of symptomatic joints. Irrespective of age and obesity, multiple symptomatic joints were the rule, not the exception. It was notable that the frequency of co-occurring conditions increased with increasing symptomatic joint count. This may suggest a need to re-examine how OA is characterized and perhaps its underlying etiology as it relates to single vs. multi-joint involvement. Disclosure of Interest: None declared